2016
DOI: 10.1007/s11682-016-9621-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between years of education, regional grey matter volumes, and working memory-related brain activity in healthy older adults

Abstract: The aim of this study was to examine the relationships between educational attainment, regional grey matter volume, and functional working memory-related brain activation in older adults. The final sample included 32 healthy older adults with 8 to 22 years of education. Structural magnetic resonance imaging (MRI) was used to measure regional volume and functional MRI was used to measure activation associated with performing an n-back task. A positive correlation was found between years of education and cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 61 publications
6
44
0
2
Order By: Relevance
“…This agrees with earlier observations that showed significant differences in the FC of these regions between aMCI, AD, and HC subjects [54, 55]. These regions are related to goal-directed action and compensatory cognitive function [56-58], being classified as the same functional community by functional parcellation [59]. Moreover, they are known to be components of a salience network that plays a regulatory role between AD-vulnerable and compensatory networks [56, 60].…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with earlier observations that showed significant differences in the FC of these regions between aMCI, AD, and HC subjects [54, 55]. These regions are related to goal-directed action and compensatory cognitive function [56-58], being classified as the same functional community by functional parcellation [59]. Moreover, they are known to be components of a salience network that plays a regulatory role between AD-vulnerable and compensatory networks [56, 60].…”
Section: Discussionsupporting
confidence: 92%
“…The observed association between YoE and higher cortical thickness in medial prefrontal, ACC, and orbitofrontal cortices provides further converging evidence to other neuroimaging studies conducted within the CR model (Arenaza-Urquijo et al, 2013;Kim et al, 2015;Lee et al, 2016;Boller et al, 2017;Vaqué-Alcázar et al, 2017). The relevance of distinct frontal lobe areas as mediators of CR mechanisms is probably related to their key role in cognitive processes such as working memory (Owen et al, 2005;Barbey et al, 2011), cognitive conflict monitoring (Jahn et al, 2016), or decision-making (Shenhav et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…Selection of the covariates was based on previous work that has shown that age (e.g., Peters, ), sex (e.g., Taki et al., ), socioeconomic status (e.g., Piccolo et al., ), education (e.g., Boller et al., ), use of tobacco (e.g., Durazzo et al., ), and cannabis and other drug use (e.g., Li et al., ; Lopez‐Larson et al., ) are significantly associated with variation in cortical thickness. Twin status (i.e., monozygotic or not; dizygotic or not) was included given the twin enrichment of the HCP dataset.…”
Section: Methodsmentioning
confidence: 99%